HISTO-CHEMICAL GROUND OF TERTIARY HUMAN ENAMEL BIOMINERALIZATION PROCESS - Gasiuk, P.A.; Gasiuk, N.V. (World of Medicine and Biology, 2012)
Presence of investigated four zones describes the stage-by-stage protein replacement, i.e. enamelin with hydroxyl apatite crystals, which are developed during incoming from salivary secret after teeth eruption.
Keywords: histo-chemistry; slices; enamel; biomineralization